Comparing cervical mucus changes in response to an oral progestin or oestrogen withdrawal in ovarian-suppressed women: a clinical pilot. (4th May 2019) - Han, Leo; Padua, Emily; Hart, Kyle D.; Edelman, Alison; Jensen, Jeffrey T.
Abstract: Purpose: Prior studies evaluating the effect of administered progestogens on peak cervical mucus have not controlled for the influence of endogenous hormones. To address this, we treated women with a gonadotropin-releasing hormone (GnRH) agonist to suppress the hypothalamus–pituitary–ovarian (HPO) axis and used transdermal oestradiol replacement to stimulate peak cervical mucus and then evaluated the effects of an oral progestin or oestradiol withdrawal. Materials and methods: We used a crossover design to examine cervical mucus changes in women receiving transdermal oestradiol replacement following intramuscular administration of leuprolide acetate. After increasing oestradiol patches to mid-cycle levels, subjects were assigned to either 0.35 mg oral norethindrone with continuation of the patches (NET) or oestradiol withdrawal by patch removal (E2WD). We collected serum and cervical mucus samples at 0, 2, 4, 6, 22 and 24 h following the intervention. Results: We analysed 12 cycles (6 NET, 6 E2WD) from three subjects. Baseline cervical mucus scores were favourable to sperm penetration [NET median 11, interquartile range (9–12), E2WD 13 (12–13)]. Two hours after removal of oestradiol patch or administration of norethindrone, cervical mucus scores declined [NET 8.5 (4–9), E2WD 10.5 (10–12)]. Low cervical mucus scores persisted at 24 h with NET [8.0 (7–8)] but not E2WD [10.5 (8–11)]. Conclusions: We observed a rapid decline in cervical mucus Insler scores following administration of a single dose of oral norethindrone, and scores remained lower and unfavourable through 24 h. Oestradiol withdrawal did not result in similar unfavourable changes.